Crystal Structure Characterization of Fe3O4 Nanoparticles Synthesized via the Co-precipitation Method Using X-Ray Diffraction - Siti Fuziyawati Ishak; Yus Rama Denny; Yuvita Oktarisa (IAIN Sorong, 2026)
The use of Fe₃O₄ magnetic iron oxide nanoparticles in various technological applications is on the rise, but their performance is significantly influenced by their phase purity and degree of crystallinity. The coprecipitation method is simple and capable of producing a wide range of crystalline characteristics, thus warranting further investigation. This study aims to identify the crystal structure of Fe₃O₄ nanoparticles synthesised via coprecipitation using X-ray diffraction (XRD). The focus is on determining the crystal phase, identifying the characteristic diffraction patterns of magnetite, and measuring the crystallite size. Synthesis was carried out by mixing Fe³⁺ and Fe²⁺ in a 2:1 ratio using FeCl₃.6H₂O and FeSO₄.7H₂O. Subsequently, 10% NH₄OH was added at 60 °C with continuous stirring at 600 rpm for 90 minutes. Following this, the material was washed seven times and dried at 100 °C for 2 hours. The material was then characterised using XRD. The results of the study showed that Fe₃O₄ nanoparticles were successfully synthesised in the form of a dense black powder. The XRD diffraction pattern showed six distinct magnetite peaks at 2θ angles of approximately 30.2°, 35.6°, 43.3°, 53.2°, 57.3° and 62.7°, corresponding to the crystal planes (220), (311), (400), (422), (511) and (440) according to the JCPDS database. This indicates the formation of a spinel structure with good crystallinity. Furthermore, a small amount of hematite (Fe₂O₃) impurity phase was detected. Calculations using the Debye–Scherrer equation indicate an average crystal size of 10 nanometres. These results demonstrate that the coprecipitation method is effective for producing nano-sized Fe₃O₄ nanoparticles with a well-defined crystal structure, which hold potential for development in various magnetic material applications.